Synthesis of Novel Gefitinib-Conjugated 1,2,3-Triazole Derivatives and Their Effect of Inducing DNA Damage and Apoptosis in Tumor Cells - Junfei Wu; Xu Huang; Shan Lu; Ziyi Wang; Longfei Mao; Sanqiang Li (Molecules)
Compounds with rigid planar structures can insert into tumor cell DNA, thereby inducing DNA damage in tumor cells. In this study, quinazoline, a compound with a planar structure, was used as the core scaffold. A rigid planar 1,2,3-triazole moiety was introduced into its structure, and its activity was tested on HepG2 liver cancer cells. The results showed that most compounds exhibited inhibitory effects on HepG2 cells, and the IC50 values of the most effective compounds were 3.08 ± 0.37 μM and 3.60 ± 0.53 μM. We found that the designed compounds significantly upregulated the expression of γ-H2AX in tumor cells, inducing DNA damage while reducing PARP levels, thereby weakening the DNA damage repair capacity of tumor cells and leading to apoptosis. Additionally, these compounds inhibited the migration and invasion of HepG2 cells. One of the compounds was found to be low in toxicity in mice, suggesting its potential as a targeted DNA anti-tumor drug.